Tibial anatomy in normal small breed dogs including anisometry of various extracapsular stabilizing suture attachment sites - Witte, P. G. (Veterinary and Comparative Orthopaedics and Traumatology, 2015)
Objectives: To investigate proximal tibial anatomy and its influence on anisometry of extracapsular stabilizing sutures in small dog breeds.Materials and methods: Mediolateral radiographs of the femora, stifles, and tibiae of 12 small breed dogs were acquired with the stifles positioned at various angles. Measurements taken included tibial plateau angle (TPA), diaphyseal: proximal tibial angle (DPA), patellar tendon angle (PTA), Z-angle, relative tibial tuberosity width (rTTW), and the distance between six combinations of two femoral and three tibial extra-capsular stabilizing suture (ECS) attachment sites. Theoretical strain through stifle range-of- motion was recorded.Results: The TPA (32° ± 5.8°), DPA (10.2° ± 7.3°), PTA (103.7° ± 6.2°), and Z-angle (70.4° ± 9.0°) were positively correlated with one another (R >0.7), but none were correlated with rTTW (0.93 ± 0.10). The F2-T1 combination of ECS attachment sites had lowest strain for nine stifles. The shortest attachment site separation was at a stifle flexion of 50° for nine stifles. Proximal tibial anatomy measurements could not predict optimal attachment site combination, optimal stifle angle for suture placement, or ECS strain.Clinical significance: There is individual variation in the optimal attachment site combination and stifle angle for suture placement, which may influence consistency of outcomes with ECS.
Keywords: Cranial cruciate ligament rupture; isometry; extracapsular suture; tibial plateau angle; TPA; diaphyseal proximal tibial angle; DPA